Preliminary Assessment of Telemedicine Systems using Virtual Testbed - Anak Agung Ngurah Ananda Kusuma; Tahar Agastani; Muhammad Iqbal; Triawan Nugroho (IJNMT (International Journal of New Media Technology), 2019)
Telemedicine is the use of ICT (Information and Communication Technology) infrastructures to provide medical services. It is needed in Indonesia, particularly in remote areas where the number of medical facilities and specialist doctors are limited. BPPT has developed telemedicine systems which can provide tele-ECG, tele-USG, and tele-Consultation. Its feasibility requires some verification on its intended operations. This paper presents a virtual testbed for testing telemedicine systems, and shows some assessment results on their security and performance aspects.